Implementation of Community Service Order Based on Law Number 1 of 2023 In The Perspective of Justice And Legal Expediency - Fahreshi Arya Pinthaka; Ali Masyhar; Cahya Wulandari (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
This research is related to the reform of criminal law in Indonesia through community service order as an alternative to imprisonment. The type of research used in this study is normative legal research. The specifications used in this legal research are descriptive analytical, with a statute approach and a conceptual approach. The types of legal materials used in this research are primary and secondary legal materials. The method of collecting legal materials used by the author in this research is literature study. The method of legal material analysis conducted in this research uses qualitative analysis. The results of this research show that based on Law Number 1 of 2023 concerning the Criminal Code (KUHP), community service order is one of the main types of penalties that also serves as an alternative to short-term imprisonment, specifically for criminal offenses with a potential penalty of less than five years and where the judge imposes a maximum prison sentence of 6 (six) months. It also serves as a substitute for fines that do not exceed category II. This is an implementation of community service order to achieve the objectives of punishment and with the perspectives of justice and legal expediency.